Forest Management and Water Resources in the Anthropocene - James M. Vose (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
Decades of research has provided a depth of understanding on the relationships among forests and water, and how these relationships change in response to climate variability, disturbance, and forest management. This understanding has facilitated a strong predictive capacity and the development of best management practices to protect water resources with active management. Despite this understanding, the rapid pace of changes in climate, disturbance regimes, invasive species, human population growth, and land use expected in the 21st century is likely to create substantial challenges for watershed management that may require new approaches, models, and best management practices. These challenges are likely to be complex and large scale, involving a combination of direct effects and indirect biophysical watershed responses, as well as socioeconomic impacts and feedbacks. We explore the complex relationships between forests and water in a rapidly changing environment, examine the trade-offs and conflicts between water and other resources, and examine new management approaches for sustaining water resources in the future.